Serro e Diamantina coloniais: uma releitura da prática musicológica de Curt Lange - Rachel Tupynambá de Ulhôa (2022)
The general objective of the dissertation is to evaluate the musicologist practice of Francisco Curt Lange (1903-1997) through his research documents (consulted bibliography, sent correspondence and registry documents), on music in colonial Serro and Diamantina. The text is divided in four independent chapters, so that each chapter develops specific objectives, progressively articulated towards the intended evaluation. Each chapter utilizes references that are pertinent to the matter, mainly on the perspective of musicology (Modesto Flávio Fonseca, 2013 e Paulo Castagna, 2004; 2008a; 2008b), with complementary resource of history, especially the concept of monument-document by Jacques Le Goff (2013) and of self-writing, developed by Ângela de Castro Lopes (2004). In the first chapter we seek to understand the bibliography on colonial period Minas music, published between 1940 and 2020, identifying the main authors, formats and categories. In the second chapter, we intend to reconstruct the chronology and specificities of Curt Lange’s research trajectory on musical practice in colonial Serro and Diamantina, based on the analysis of correspondence from 1956 to 1986, sent by the musicologist to people directly connected to the place, as well as facilitators of the publication of his research results. In the third chapter we access the basic bibliography used by Lange when he worked on the text of Book VIII of Collection of History of Music in the General Province of Minas Gerais (Coleção História da música na Capitania Geral de Minas Gerais) dedicated to Vila do Príncipe do Serro Frio and Arraial do Tejuco, highlighting his main arguments, choices and emphasis. Finally, in the fourth chapter we seek to update the interpretation of data contained in the documents referring to musical practice in colonial Serro and Diamantina, collected and stored in the Curt Lange Archives at UFMG – ACL/UFMG (Series 10 – Subseries 10.3 – Folders 10.3.35 and 10.3.39). The thesis we adopt is that Curt Lange wrote a partial history of music in colonial Serro and Diamantina, while focusing his interpretation on the life and oeuvre of one single compositor, who he considered as comparable to the great European compositors. By doing so, he limited his vision on the register of musical practices contained in the researched registry documents, with considerable impact on his interpretation of the social standing of mixed race musicians in colonial Minas. We consider that Lobo de Mesquita, in no detriment to the aesthetic-musical quality of his oeuvre, was a mixed race person who exerted the office of music, being subjected to the weight of his condition as a craftsman, in the context of class society of the period. Against the emancipating and even glamorous vision proposed by the musicologist, the reinterpretation of data points rather to a relation of dependence and subordination, both among musicians and the layman organizations at the time, as also among the musicians and the Chamber Senate. Furthermore, we conclude that the historical narrative proposed by Curt Lange is not the only one to be told, since we have found indications of other histories of music in colonial Serro and Diamantina, which are still to be investigated.